Soil contamination of agricultural land with strontium-90: dynamics and spatial distribution - Tsybulka, Mikalai; Zhuravkov, Vladislav; Tsyribko, Viktor; Alekseychik, Elena (Journal of the Belarusian State University. Ecology, 2024)
The analysis of dynamics, current state and spatial distribution of strontium-90 contaminated soils of arable and meadow lands based on the last round of their survey is presented. For a long post-accident period, the areas of lands contaminated with strontium-90 have decreased twice as a result of natural decay of radionuclides. At present, agricultural production is carried out on 271,06 thousand hа of lands contaminated with this radionuclide with the density of contamination 0,15–3,00 Ci/km2 that makes about 3,6 % of the total area of agricultural land of the republic. The ratio of the areas and distribution of agricultural lands by densities of radioactive contamination has significantly changed. The share of land with density of contamination 0,15–0,30 Ci/km2 is 62 % from the total area of the lands; with density of 0,31–1,00 Ci/km2 – 34 % and with density of 1,01– 3,00 Ci/km2 – 4%. The contaminated with 90Sr land is mainly situated in the Gomel region (96 %). By administrative districts the share of contaminated lands varies from less than 0.1 to 96.4 % of the total area of agricultural land in the district. In agrarian land use in 11 districts there are 103,2 thousand ha of lands contaminated with strontium-90 with density of 0,31–3,00 Ci/km2, where exceeding of reference levels of radionuclide content in crop production, first of all, in grain for food purposes is observed. The areas of such lands vary widely by districts, however, the main massifs of such lands are concentrated in Bragin (39.5 thousand ha) and Khoyniki (37.8 thousand ha) districts of Gomel region. These two districts contain 75 % of all arable and meadow lands contaminated with strontium-90 with density higher than 0.30 Ci/km2.